2016
DOI: 10.1002/prp2.249
|View full text |Cite
|
Sign up to set email alerts
|

RGS14 regulates the lifetime of Gα‐GTP signaling but does not prolong Gβγ signaling following receptor activation in live cells

Abstract: RGS14 is a multifunctional scaffolding protein possessing two distinct G protein interaction sites including a regulator of G protein signaling (RGS) domain that acts as a GTPase activating protein (GAP) to deactivate Gαi/o‐GTP proteins, and a G protein regulatory (GPR) motif that binds inactive Gαi1/3‐GDP proteins independent of Gβγ. GPR interactions with Gαi recruit RGS14 to the plasma membrane to interact with Gαi‐linked GPCRs and regulate Gαi signaling. While RGS14 actions on Gα proteins are well character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…RGS14 integrates signaling through multiple GTPases by binding active G␣ i/o subunits (4), inactive G␣ i1 and G␣ i3 (5), and small GTPases, including active H-Ras (6,7) and Rap2 (8). Besides binding G␣ i/o at its RGS domain, RGS14 also interacts with GDP-bound G␣ i1/3 subunits at its G protein regulatory (GPR) motif (4,5,9,10). Although RGS14 was originally discovered as a Rap-binding protein via its R1 Raf-like Ras/Rapbinding domain, studies suggest that RGS14 likely interacts preferentially with active H-Ras in cells (6,7).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RGS14 integrates signaling through multiple GTPases by binding active G␣ i/o subunits (4), inactive G␣ i1 and G␣ i3 (5), and small GTPases, including active H-Ras (6,7) and Rap2 (8). Besides binding G␣ i/o at its RGS domain, RGS14 also interacts with GDP-bound G␣ i1/3 subunits at its G protein regulatory (GPR) motif (4,5,9,10). Although RGS14 was originally discovered as a Rap-binding protein via its R1 Raf-like Ras/Rapbinding domain, studies suggest that RGS14 likely interacts preferentially with active H-Ras in cells (6,7).…”
mentioning
confidence: 99%
“…Although RGS14 was originally discovered as a Rap-binding protein via its R1 Raf-like Ras/Rapbinding domain, studies suggest that RGS14 likely interacts preferentially with active H-Ras in cells (6,7). RGS14 also interacts with both G protein-couple receptors and the nonreceptor guanine nucleotide exchange factor Ric-8A in a G proteindependent manner (6,10,11). Whereas RGS14 interacts with multiple signaling proteins at the plasma membrane, we and others have shown that RGS14 is also a nucleocytoplasmic shuttling protein (5,(12)(13)(14), suggesting it serves as yet undefined roles in the nucleus.…”
mentioning
confidence: 99%
“…In fact, RGS12 could not only have pivotal physiological functions as a signaling www.nature.com/scientificreports/ regulator but was considered to be a potential therapeutic target for airborne particulate matter (PM2.5) or bacterial infection-induced airway inflammation (our unpublished data) 31 . Based on our results, we hypothesized that (i) RGS12 is activating to maintain homeostasis in inflamed conditions induced by LPS, (ii) RGS12 has a PDZ domain near the N-terminal region that recruits PDZ-binding proteins or PDZ-containing regulatory proteins such as ZO-1 32 , or (iii) RGS12 also has GPR (also known as GoLoco) motif 33 . The GPR motif binds to the Gαi protein and has GTPase activity.…”
Section: Discussionmentioning
confidence: 97%
“…These studies provided a structural basis for the experimentally confirmed ability of GIV to displace GβƔ from Gai in cells , where it dissociates the Gi heterotrimer and triggers Gai and GβƔ signaling (Midde, Aznar et al 2015). To determine if binding of GIV-L to Gai that we observe in vitro actually translates into G protein signaling in cells, we utilized a bioluminescence resonance energy transfer (BRET) assay measuring the association between luciferase-tagged Gai and mVenus-tagged GβƔ (Figure 3E) (Breton, Sauvageau et al 2010, Brown, Lambert et al 2016. In this assay, a loss of BRET signal indicates GbƔ dissociation from the G-alpha subunit and, therefore, activation of the G-protein.…”
Section: Solved Structures Of Giv-bound Gai Have Confirmed That Giv Ementioning
confidence: 99%
“…mVenusCT-hGBB1 and mVenusNT-hGBG2 were a gift from Nevin Lambert, Univ. of Alberta (Brown, Lambert et al 2016). pcDNA3.1(+)-hGai1(91)-RLuc2 was generously shared by Michel…”
Section: Bret-based Assessment Of Gai/gβɣ Dissociationmentioning
confidence: 99%